Effect of passive ultrasonic irrigation on Enterococcus faecalis from root canals: An ex vivo study - Guerreiro-Tanomaru, Juliane Maria [UNESP]; Chávez-Andrade, Gisselle Moraima [UNESP]; de Faria-Júnior, Norberto Batista [UNESP]; Watanabe, Evandro; Tanomaru-Filho, Mário [UNESP] (FapUNIFESP (SciELO), 2015)
Endodontic irrigation aims to clean and disinfect the root canal system. Passive ultrasonic irrigation (PUI) is based on the use of an ultrasound-activated instrument into the root canal filled with irrigant. The aim of this study was to evaluate, ex vivo, the effectiveness of PUI in eliminating Enterococcus faecalis from root canals. Seventy-five extracted human single-root teeth were used. After root canal preparation, specimens were inoculated with E. faecalis and incubated at 37 °C for 21 days. Specimens were distributed into five groups (n=15), according to the irrigation method: PUI + saline solution (PUI/SS); PUI + 1% NaOCl (PUI/NaOCl); conventional needle irrigation (CNI) + saline solution (CNI/SS); CNI + 1% NaOCl (CNI/NaOCl); No irrigation (control). Microbiological samples were collected at three time points: initial (21 days after inoculation), post-irrigation (immediately after irrigation), and final (7 days after irrigation). Data were obtained in CFU mL-1 and subjected to analysis by ANOVA and Tukey’s tests at 5% significance level. The post-irrigation samples did not demonstrate statistical difference between PUI/SS and CNI/SS nor between PUI/NaOCl and CNI/NaOCl (p>0.05), but PUI/NaOCl and CNI/NaOCl had lower CFU mL-1 number than the other groups (p>0.05). Statistically significant difference was observed between the initial and post-irrigation samples and between the post-irrigation and final samples (p<0.05) in all groups, except in the control. The final samples of all groups presented bacterial counts similar to the initial samples. PUI or CNI with 1% NaOCl contribute to disinfection, but are unable to eradicate E. faecalis from the root canal system.
Keywords: Endodontics; Enterococcus faecalis; Passive ultrasonic irrigation; Root canal disinfection